Pengaruh Intellectual Capital Terhadap Kinerja Keuangan Perusahaan Perbankan Yang TerdaftarDi Bursa Efek Indonesia (BEI) - Aga, Octa Nilam Lukkita (2016)
ABSTRACT The principal purpose of this study was to investigate the association between the efficiency of value added major components based on the company's resources ( physical capital, human capital and structural capital) and four traditional dimensions of financial companys performance: ROA, ATO, GR and ASR. Data were drawn from 81 banking in Indonesia for three periods, 2012-2014. This study examined the three elements of VAICTM and measures financial performance by using partial least squares (PLS) for data analysis. The findings of this study indicate that there is a positive effect of physical capital (VACA) the financial performance of the company, there is a positive effect of human capital (VAHU) the financial performance of the company, the positive effect of structural capital (STVA) on the performance of the company's financial and intellectual capital (VAICTM) the financial performance of the company. The empirical findings of this study stated that the Physical Capital (VAIC), Human Capital (VAHU), Structural Capital (STVA), ATO and GR is a significant indicator for VAICTM and financial performance. Keywords : Intellectual Capital, Physical Capital, Human Capital, Structural Capital, Value Added Intellectual Coefficients (VAICTM), Company Financial Performance, Bank Indonesia, and Partial Least Squares.